IMPROVING LEARNING OUTCOMES FOR SIMPLE GEOMETRIC NETS USING A PROJECT-BASED LEARNING (PJBL) MODEL INTEGRATED WITHDEEP LEARNING IN FIFTH-GRADE PRIMARY SCHOOL - Annisa Olivia Memosa; Masniladevi; Syafri Ahmad; Melva Zainil (SOSIOEDUKASI, 2026)
This research is motivated by the low mathematics learning outcomes of fifth-grade students at an elementary school in Padang, especially on the topic of geometric nets. Preliminary data shows that only 15% of students achieve the minimum completion criteria. This research aims to improve student learning outcomes by implementing the Project Based Learning (PjBL) model integrated with the principles of Deep Learning (Mindful, Meaningful, and Joyful Learning). The methodology used is the Classroom Action Research (CAR) model of Kemmis and McTaggart which consists of planning, implementation, observation, and reflection stages. The research subjects were 20 fifth-grade students. Data collection was carried out through observation, interviews, and tests, which were analyzed using qualitative and quantitative techniques (mixed-methods). The results of the study showed a significant increase in the quality of learning and student achievement. Teacher activity scores increased from 86.11% in Cycle I to 94.44% in Cycle II, while student activity increased from 83.33% to 91.67%. Furthermore, the average student learning outcomes increased from 69.5 in Cycle I to 81.13 in Cycle II, with a completion percentage reaching 80%. It can be concluded that the Deep Learning integrated PjBL model effectively improves learning outcomes for elementary school students on spatial nets by transforming abstract concepts into concrete projects.